Dual agency problems in family firms: Evidence from director elections - Ashraf, Rasha; Li, Huimin; Ryan, Harley E. (Journal of Corporate Finance, 2020)
We use director elections to analyze outsider shareholder perspectives of agency problems in family firms. Compared to nonfamily firms, outsider shareholders in family firms provide weaker support for director slates proposed by the firms’ nominating committees. Outside shareholder support decreases when families receive private benefits of control, when family members serve in leadership roles, or when family members serve on board monitoring committees. We do not find similar results for other actively engaged concentrated owners. Our results provide new insights into outsider shareholders’ satisfaction with family control in publicly held firms and their perceptions of the family-outsider agency conflicts.